Deixis in Garuda Indonesia’s Advertisement: “Garuda Indonesia For A Better Life” - Ni Kadek Dian Ayu Purnami (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This study looks at the deixis used in the commercial "Garuda Indonesia For A Better Life," emphasizing how it works and how it affects the story. In advertising, deixis, a basic language characteristic, is vital in determining meaning and audience involvement. The study classifies and examines the personal, geographical, and temporal deixis used in advertising using Yule's deixis paradigm. To investigate how deixis creates meaning, encourages emotional connection, and strengthens the commercial's persuasive appeals court, data were gathered through document examination of the advertisement text using a descriptive qualitative technique. The results show that first-person deixis is more common, which has consequences for our comprehension of customer behavior and the efficacy of advertising tactics.